Strategic Analysis of the Development of Renewable Energetics in the World and in Ukraine - Valentyna Yakubiv; Iryna Boryshkevych (Vasyl Stefanyk Precarpathian National University, 2019)
The article analyses tendencies in changes in power supply volumes in world countries for the last years. We identified tendencies in changes of power supply volumes in the context of different sources of its production. We studied the tendencies of development of renewable energetics in the world and in Ukraine. We based the potential of the development of renewable energetics in the world and in Ukraine. We conducted complex analysis of strategic perspectives of the development of renewable energetics in Ukraine on the basis of PEST-analysis. We also based the main trends of strategic changes in the industry in the framework of the most powerful external factors of influence the development of renewable energetics. We offered the complex of strategic measures within the limits of the most influential environmental factors within PEST-analysis.